EXTENT OF GOVERNMENTâ€™S INVOLVEMENT IN PROMOTING INCLUSIVE EDUCATION FOR BASIC EDUCATION DELIVERY IN OWEERI MUNICIPAL COUNCIL, IMO STATE - Ekweozor, Chidimma E.; Bosah, Chukwuebuka N.; Elechi, Gift O. (Journal of Early Childhood and Primary Education, 2020)
This study investigated the extent of governmentâ€™s involvement in promoting inclusive education for Basic education delivery in Owerri municipality, Imo state. A descriptive survey design was adopted. Three research questions guided the study. All the 142 pre-primary school teachers in the 24 government owned pre-primary schools in Owerri Municipality were used for the study, hence there was no sampling because all the participants were used due to the small number of the population. A 30 item Questionnaire titled â€œExtent of Governmentâ€™s Involvement in Promoting Inclusive Education for Basic Education Deliveryâ€ (EGIPIEBED) was used to collect the data. The instrument was validated by 3 research experts. The data collected were analysed using mean. A gross reliability coefficient of 0.67 was obtained using Cronbach-Alpha method. The major findings of the study were that extent of governmentâ€™s involvement in providing human and material resources for promoting inclusive education is of low extent. Also, the government is lagging behind in rendering some services that are deemed fit for effective inclusive education. Based on the findings, it was recommended that government should endeavour to employ adequate and qualified human resources needed for effective inclusive education. Also government should provide the necessary material resources needed for promoting inclusive education.
Keywords: Education; Inclusive education; Basic education